Association between body mass index (BMI) and hypertension in south Asian population: evidence from nationally-representative surveys - Fariha Binte Hossain; Gourab Adhikary; Ariful Bari Chowdhury; Md Shajedur Rahman Shawon (BMC, 2019)
Abstract Background Although there has been a well-established association between overweight-obesity and hypertension, whether such associations are heterogeneous for South Asian populations, or for different socioeconomic groups is not well-known. We explored the associations of overweight and obesity using South Asian cut-offs with hypertension, and also examined the relationships between body mass index (BMI) and hypertension in various socioeconomic subgroups. Methods We analysed the recent Demographic and Health Survey (DHS) data from Bangladesh, India, and Nepal, with a total of 821,040 men and women. Hypertension was defined by 2017 ACC/AHA cut-offs and by Joint National Committee 7 (JNC7) cut-offs for measured blood pressure and overweight and obesity were defined by measured height and weight. We used multiple logistic regressions to estimate the odds ratios (ORs) with 95% confidence intervals (CIs) of hypertension for overweight and obesity as well as for each 5-unit increase in BMI. Results The prevalence of hypertension using JNC7 cut-offs among participants increased by age in all three countries. The prevalence ranged from 17.4% in 35-44 years to 34.9% in ≥55 years in Bangladesh, from 4.6% in 18-24 years to 28.6% in 45-54 years in India, and from 3.8% in 18-24 years to 39.2% in ≥55 years in Nepal. Men were more likely to be hypertensive than women in India and Nepal, but not in Bangladesh. Overweight and obesity using both WHO and South Asian cut-offs were associated with higher odds of hypertension in all countries. For each 5 kg/m2 increase in BMI, the ORs for hypertension were 1.79 (95% CI: 1.65-1.93), 1.59 (95% CI: 1.58-1.61), and 2.03 (95% CI: 1.90-2.16) in Bangladesh, India, and Nepal, respectively. The associations between BMI and hypertension were consistent across various subgroups defined by sex, age, urbanicity, educational attainment and household's wealth index. Conclusions Our study shows that the association of BMI with hypertension is stronger for South Asian populations at even lower cut-offs points for overweight and obesity. Therefore, public health measures to reduce population-level reduction in BMI in all population groups would also help in lowering the burden of hypertension.